2015
DOI: 10.1371/journal.pone.0142709
|View full text |Cite
|
Sign up to set email alerts
|

Digital Presence of Norwegian Scholars on Academic Network Sites—Where and Who Are They?

Abstract: The use of academic profiling sites is becoming more common, and emerging technologies boost researchers’ visibility and exchange of ideas. In our study we compared profiles at five different profiling sites. These five sites are ResearchGate, Academia.edu, Google Scholar Citations, ResearcherID and ORCID. The data set is enriched by demographic information including age, gender, position and affiliation, which are provided by the national CRIS-system in Norway. We find that approximately 37% of researchers at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
50
4
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 24 publications
14
50
4
5
Order By: Relevance
“…Our study would help us understand whether ResearchGate was competing with our IR for faculty-authored content. It would also provide insights that could lead to improvements in our implementation of the OA Policy and greater success in recruiting faculty content.We chose to compare the faculty's OA Policy compliance with their participation in ResearchGate specifically-rather than Academia.edu or other sites-primarily because ResearchGate has been shown to be the most popular academic social network among scholars Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali, Nicholas, & Herman, 2016;Matthews, 2016; MeisharTal & Pieterse, 2017;Mikki, Zygmuntowska, Gjesdal, & Al Ruwehy, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our study would help us understand whether ResearchGate was competing with our IR for faculty-authored content. It would also provide insights that could lead to improvements in our implementation of the OA Policy and greater success in recruiting faculty content.We chose to compare the faculty's OA Policy compliance with their participation in ResearchGate specifically-rather than Academia.edu or other sites-primarily because ResearchGate has been shown to be the most popular academic social network among scholars Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali, Nicholas, & Herman, 2016;Matthews, 2016; MeisharTal & Pieterse, 2017;Mikki, Zygmuntowska, Gjesdal, & Al Ruwehy, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014). …”
mentioning
confidence: 99%
“…Nature found that just under half of the more than 3,500 scientists and engineers they surveyed visit ResearchGate regularly (Van Noorden, 2014), while a recent survey of over 20,000 respondents by researchers at Utrecht University Library found that 61% who have published at least one paper use ResearchGate Matthews, 2016). Other measures of the proportion of researchers using ResearchGate range from 15% to 65% depending on the population studied (Campos & Valencia, 2015;Haustein et al, 2014;Laakso et al, 2017;Lupton, 2014;Madhusudhan, 2012;Mahajan, Singh, & Kumar, 2013;Meishar-Tal & Pieterse, 2017;Míguez-González, Puentes-Rivera, & Dafonte-Gómez, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017).A number of studies have reported that ResearchGate is relatively more popular among researchers in the sciences when compared with the academic social network Academia. edu, which is preferred by researchers in the social sciences and especially the humanities Campos-Freire & Rúas-Araújo, 2016;Elsayed, 2015;Jamali et al, 2016;Matthews, 2016;Mikki et al, 2015;Nández & Borrego, 2013;Ortega, 2015;Thelwall & Kousha, 2015;Thelwall & Kousha, 2017;Van Noorden, 2014 Míguez-González et al, 2017;Mikki et al, 2015;Ortega, 2015;Singh, 2016;Tran & Lyon, 2017;Van Noorden, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…REPÈRES médecine/sciences 2017 ; 33 : 647-52 médecine/sciences de ces deux plateformes [4][5][6][7]. Un tel développement s'explique en partie par leur utilisation des codes du web 2.0 3 [8,9] (➜), à commencer par la facilité d'utilisation et la gratuité, mais surtout par leur insertion dans l'écosystème académique.…”
Section: Perspective / Horizonsunclassified
“…Most researchers still do not manage their academic profiles in an efficient, careful, updated and complete way, according to a study by the University of Bergen (Mikki, Zygmuntowska, Gjesdal et al, 2015). Studies on collective intelligence and social search have identified the behaviour patterns and the taxonomies centred in the user (McDonnell and Siri, 2011).…”
Section: Educational Use Of Social Networkmentioning
confidence: 99%